2010
DOI: 10.1055/s-0029-1245275
|View full text |Cite
|
Sign up to set email alerts
|

Krefeld CONTRA Study: Conventional Peroral Esophago-Gastro-Duodenoscopy (EGD) vs. Transnasal EGD – a Prospective and Randomised Study with Independent Evaluation of Conscious Sedation, Endoscope Diameter, and Access Path

Abstract: Unsedated transnasal EGD may replace diagnostic peroral EGD, reduces costs with acceptable patient discomfort and has advantagous acceptability of the endoscopic staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…In the intra-individual control group 3 (TON-EGD), 4 out of 5 patients rated a TN-EGD to be more acceptable than the previously experienced TO-EGD and would ask for a TN-EGD in the future. Similar results were found before [2,3,11,13,14,18]. Thin endoscopes have been used also for TO-EGD and tolerance was found to be the same as for TN-EGD [15,19].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In the intra-individual control group 3 (TON-EGD), 4 out of 5 patients rated a TN-EGD to be more acceptable than the previously experienced TO-EGD and would ask for a TN-EGD in the future. Similar results were found before [2,3,11,13,14,18]. Thin endoscopes have been used also for TO-EGD and tolerance was found to be the same as for TN-EGD [15,19].…”
supporting
confidence: 86%
“…Thus, professional endoscopic societies have published guidelines [26 -28] that require a qualified assistant during a procedure under sedation, as well as monitoring of vital signs for 1 -2 hours afterwards. Resources in form of equipment, manpower and a recovery room as well as the inability for legal decisions and taking part in traffic for 12 -24 hours, cause sedation to crave resources and produce higher costs [7,13].…”
mentioning
confidence: 99%
“…Inspection of the mucosa is performed by pulling the endoscope slowly upward in a circumferential manner. For inspection of the esophagus, air is blown through the working channel to open the esophagus . The gastrointestinal junction is difficult to inspect and requires more time.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that after 1 year, the initial costs of purchasing the esophagoscope were fully met and from there on, £230 (82%) per patient is saved. Frieling et al found pharmaceutical cost reduction of [euro]18.489 per year for unsedated TN‐EGD compared to sedated TN‐EGD. Potential cost savings could come from reduction in radiology (barium swallow ± £150), follow‐up (±£80) and esophagoscopy in general anesthesia (±£450) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation